Shoulder Balance in Adult Spinal Deformity Patients Undergoing Selective Lumbar Fusion. Issue 9 (1st May 2022) - Alluri, Ram Kiran; Sheikh, Basel; Elysee, Jonathan Charles; Lovecchio, Francis; Shah, Sachiin; Punyala, Ananth; Ang, Bryan; Lafage, Renaud; Lafage, Virginie; Schwab, Frank; Kim, Han Jo
Abstract : This was a retrospective study of 86 patients with adult spinal deformity undergoing selective lumbar fusion with compensatory proximal thoracic curves. Shoulder balance, as measured by the clavicle angle, did not significantly change over the postoperative period. From a functional standpoint, shoulder balance demonstrated no correlation with patient-reported outcome scores. Abstract : Study Design: Retrospective review. Objective: To analyze if shoulder balance continues to change in the postoperative period in patients undergoing selective lumbar fusion for adult spinal deformity (ASD), and secondarily, analyze if shoulder balance correlates with health-related quality of life (HRQOL) outcomes. Summary of Background Data: Shoulder balance in patients with ASD is poorly understood and has largely been extrapolated from adolescent scoliosis literature. Materials and Methods: Adult patients who underwent selective lumbar fusion (upper instrumented vertebra: Τ9–Τ12, lower instrumented vertebra: L4-Pelvis) for thoracolumbar or lumbar scoliosis (cobb angle > 30°) or sagittal plane deformity with thoracic compensatory curves (cobb angle > 10°) were identified. The clavicular angle (CA) was used to quantify shoulder balance. Shoulder balance was categorized into three groups postoperatively (balanced: CA <2°, mild imbalance: CA 2°–4°, severe imbalance: CA >4°). The average CA and proportion of patients in each shoulder balance group were compared at each postoperative period. Patients with 1-year postoperative HRQOL scores were identified. Results: Eighty-six patients were included. The preoperative CA was 2.7 ± 2.3° and did not significantly change at discharge (2.9 ± 2.4°), 6-weeks (2.5 ± 2.1°), 6-months (2.4 ± 2.2°), 1-year (2.4 ± 2.5°), or 2-years (2.3 ± 1.5°) postoperatively. The proportion of patients in each shoulder balance group did not significantly change from discharge to 6-weeks, 6-months, 1-year or 2-years postoperatively (P > 0.1). At 1-year follow-up, the CA demonstrated no significant correlation with Oswestry Disability Index, Scoliosis Research Society (SRS)-22 score, or SRS-22 subscores. There was no significant association between shoulder balance group and Oswestry Disability Index, SRS-22 score, or SRS-22 subscores. Conclusions: In patients with ASD undergoing selective lumbar fusion, shoulder balance did not change over the postoperative period. From a functional standpoint, shoulder balance demonstrated no correlation with HRQOL scores. In patients undergoing selective lumbar fusion for ASD, shoulder balance may not spontaneously correct over the postoperative period, but this may not be of functional consequence. Level of Evidence: 4